2020
DOI: 10.3390/ijms21228880
|View full text |Cite
|
Sign up to set email alerts
|

GOLPH3 Regulates EGFR in T98G Glioblastoma Cells by Modulating Its Glycosylation and Ubiquitylation

Abstract: Protein trafficking is altered when normal cells acquire a tumor phenotype. A key subcellular compartment in regulating protein trafficking is the Golgi apparatus, but its role in carcinogenesis is still not well defined. Golgi phosphoprotein 3 (GOLPH3), a peripheral membrane protein mostly localized at the trans-Golgi network, is overexpressed in several tumor types including glioblastoma multiforme (GBM), the most lethal primary brain tumor. Moreover, GOLPH3 is currently considered an oncoprotein, however it… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(9 citation statements)
references
References 105 publications
(186 reference statements)
0
9
0
Order By: Relevance
“…To study the involvement of GOLPH3 in the metabolism of glycolipids, we took advantage of the T98G cell line, a broadly used model of glioblastoma multiforme [ 35 , 36 ]. In addition, T98G cells show high levels of GOLPH3 in respect to control human astrocytes from primary culture, indicating that this cell is useful for studying the functional effects of lowering the expression of GOLPH3 [ 37 , 38 ]. First, we asked if the downregulation of GOLPH3 was associated with changes in the morphology of the Golgi complex, the main organelle in which glycolipid synthesis occurs.…”
Section: Resultsmentioning
confidence: 99%
“…To study the involvement of GOLPH3 in the metabolism of glycolipids, we took advantage of the T98G cell line, a broadly used model of glioblastoma multiforme [ 35 , 36 ]. In addition, T98G cells show high levels of GOLPH3 in respect to control human astrocytes from primary culture, indicating that this cell is useful for studying the functional effects of lowering the expression of GOLPH3 [ 37 , 38 ]. First, we asked if the downregulation of GOLPH3 was associated with changes in the morphology of the Golgi complex, the main organelle in which glycolipid synthesis occurs.…”
Section: Resultsmentioning
confidence: 99%
“…Correspondingly, α2,6 sialylation of EGFR inhibits its degradation and association with LAMP1-positive lysosomes. Prior studies have reported that glycosylation modulates EGFR degradation ( 52 , 53 , 54 ); however, the effect of ST6GAL1-mediated sialylation on EGFR degradation was previously unexplored. Likewise, this is the first report demonstrating a role for α2,6 sialylation in EGFR trafficking, to our knowledge.…”
Section: Discussionmentioning
confidence: 99%
“…GOLPH3 important for maintaining the maintenance of the Golgi ribbon structure, vesicle transport and Golgi glycosylation [ 29 , 30 ]. The role of GOLPH3 in tumorigenesis may be related to the following cellular activities: regulation of Golgi-to-plasma membrane transport and acceleration of malignant secretory phenotypes [ 31 , 32 ]; control of the internalization and circulation of key signaling molecules or increase of the glycosylation of cancer-associated glycoproteins [ 33 , 34 ]; and the influence of DNA damage response and maintenance of genomic stability [ 35 , 36 ]. GOLPH3 can promote the proliferation and inhibit the apoptosis of cancer cells via activation of the Wnt signaling pathway and can enhance the expression of β-catenin [ 37 , 38 ].…”
Section: Discussionmentioning
confidence: 99%